Local Wisdom And Regional Policy In The Implementation of Friendly Basic Service Covid 19 - Aryo Santiko; Ivan Budi Susetyo; Dwi Agustina; Eka Rofiyanti; Khairur Razikin (Ilomata International Journal of Social Science, 2021)
Local wisdom in some areas such as Aceh and West Sumatra can reduce the rate of increase in the number of people exposed by Covid-19, in this case, the local government involves the role of religious leaders and regional heads in providing firm policies so that the implementation of basic services can go well while still using the health protocol. Basic services such as education, health, public works, housing, security and order, and social affairs must continue even during the pandemic so that each region is required to have the right policies. Some regions apply the PSBB policy in order to reduce the spread of Covid-19, but even basic services in some regions experience limitations in the number of services, scope, frequency, duration, and time of service. Local Wisdom values ​​and potential regional characteristics really need to be developed in order to provide basic services that are friendly to Covid-19. Collaboration and synergy between the central and regional governments as well as between the government and stakeholders related to basic services in the midst of the Covid-19 pandemic also need to be optimized. Regions that have high covid rates, such as DKI Jakarta, East Java, and Central Java are expected to have innovative policy breakthroughs in providing basic services that are friendly to Covid-19